ISLAM DAN ADAT: TINJAUAN AKULTURASI BUDAYA DAN AGAMA DALAM MASYARAKAT BUGIS - Wekke, Ismail Suardi (Universitas Islam Negeri Raden Intan Lampung, 2013)
Islamic studies and adat (tradition) tend to enhance discourse to see how religion encounters with local culture. Recently, it shows that there are harmony and interaction between them. In addition, there is acculturation in performing religious practice in daily life. Therefore, this study will explore the interaction between Islam and adat in Bugis society in term culture acculturation. Qualitative approach was conducted during circle of research. Non-participant observation and in-depth interview were employed in collecting data. This research shows that there is synergetic on adat understanding with religious expressions. Adeq (adat) and saraq (Islamic law) both were placed as part of panggaderreng (social law). As a result, this combination gathers to rule society life. Moreover, many adat activities adapt to Islam principles. Islam was translated to local life round in preserving ethnicity existence then transform to belief spirit. Using this local potency convert a strategy to develop spirituality without Arabic characteristics. Islam in Bugis adat context interprets to norm and tradition in expanding identity Bugis society. Finally, adat and religion encounters in Bugis society culture demonstrate that there was a dialogue between them and construct a new tradition in local environment.